Analisis aliran fluida dan insulasi aliran pipa bawah laut menggunakan pipesim - Rivandy Fathur Rachman; Rosyida Permatasari (Jurnal Teknik Mesin Indonesia, 2018)
Black oil production that flows from the reservoir is always affected by water saturation and is a common problem that mainly occurs in the subsea pipeline that can form hydrate compounds. The formation of hydrate compounds in the subsea pipeline is a common problem due to significant temperature drop and thermodynamic changes during production. The problem should be effectively prevented to ensure normal pipeline operation. The purpose of this study is to find out how to reduce the formation of such compounds which can inhibit the transport process in the subsea pipeline through the use of various kinds of insulation material. The types of insulation materials tested are Polyethylene Low-Density (LDPE), Polyurethane (PU), Polypropelene (PP), Polystyrene (PS) and Polytetraflouroethylene filled with Glass (PTFE 25% GF). The fluid flow heat transfer equation in stable condition and mean heat loss is used in PIPESIM software model to analyze the selection of the insulation material required in the prevention of the formation of such compounds occurring within the subsea pipeline. The results stated that the best material of the five insulation materials used is Polystyrene (PS), whereas the worst material is Polytetraflouroethylene filled with Glass (PTFE 25% GF).